Possibility of odontoblasts activity up-regulation due to orthodontic mechanical stress in mice - Nakano, K.; Muraoka, R.; Tomida, M.; Matsuura, S.; Okafuji, N.; Siar, C.H.; Kawakami, T. (2010)
Using Waldo's method in mice, we examined the immunohistochemical expression of Runx2 and alkaline phosphatase (ALP) appearing in dental pulp cells, especially in odontoblasts, just after receiving experimental orthodontic mechanical stress, using Waldo's method in mice. The examination results demonstrated that some dental root pulp cells, especially some odontoblasts, expressed the Runx2 and ALP in a comparatively short time after receiving the stress. The results suggest that the stress may cause odontoblast activity up-regulation.